2009
DOI: 10.1158/0008-5472.can-08-2106
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Levo-1-Methyl Tryptophan and Dextro-1-Methyl Tryptophan in Reversing Indoleamine-2,3-Dioxygenase–Mediated Arrest of T-Cell Proliferation in Human Epithelial Ovarian Cancer

Abstract: It has been reported that levo-1-methyl tryptophan (L-1MT) can block indoleamine-2,3-dioxygenase (IDO) expressed by human dendritic cells (DC), whereas dextro-1-methyl tryptophan (D-1MT) is inefficient. However, whether L-1MT or D-1MT can efficiently reverse IDO-induced arrest of human T-cell proliferation has not been clarified. Here, we show a marked immunosuppressive effect of IDO derived from INDOtransfected 293 cell, IDO + ovarian cancer cells, and monocytederived DCs on CD4 + Th1 cells, CD8 + T cells, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 27 publications
1
94
0
4
Order By: Relevance
“…S3B). This activity was blocked by 1-methyl-L-tryptophan, a known IDO1 inhibitor, and not by its enantiomer 1-methyl-D-tryptophan, confirming the lack of inhibition of IDO1 by the latter (37,38). When we added mature-DC conditioned medium to CD4 þ T cells activated with coated anti-CD3 antibody, we observed that T-cell proliferation was prevented, whereas it was maintained with the immature DC-conditioned medium (Supplementary Fig.…”
Section: Characterization Of Ido1-positive Cells In Tdlnssupporting
confidence: 55%
“…S3B). This activity was blocked by 1-methyl-L-tryptophan, a known IDO1 inhibitor, and not by its enantiomer 1-methyl-D-tryptophan, confirming the lack of inhibition of IDO1 by the latter (37,38). When we added mature-DC conditioned medium to CD4 þ T cells activated with coated anti-CD3 antibody, we observed that T-cell proliferation was prevented, whereas it was maintained with the immature DC-conditioned medium (Supplementary Fig.…”
Section: Characterization Of Ido1-positive Cells In Tdlnssupporting
confidence: 55%
“…Furthermore, IDO enzymatic activity in cancer has rarely been investigated. Interestingly, researchers in an ovarian epithelial cancer study have reported IDO expression in 43% of analyzed tissues (83/ 192), and this finding was shown to be correlated with a lower tryptophan-to-kynurenin ratio in the tumor environment (38). Similar results were obtained in a study from Huang and colleagues in which they observed that lower serum tryptophan in patients with colorectal carcinoma was correlated with reduced quality of life (39).…”
Section: Discussionmentioning
confidence: 52%
“…Data reported for D-1MT, a described IDO2 inhibitor currently in clinical development, indicate that there was no decrease in plasma kynurenine levels in nonhuman primates (24) or in patients in early clinical trials (27). Multiple groups have described differences between D-1MT and L-1MT, showing that it is, in fact, L-1MT that can both decrease kynurenine generation and restore impaired proliferation of several T cell subsets and that IDO1 drives tryptophan catabolism in human dendritic cells (28,29). Hydroxyamidines, active against IDO1, suppress kynurenine generation in cells and in vivo and are therefore suitable to test the hypothesis that IDO1 inhibition may provide clinical benefit to cancer patients.…”
Section: Discussionmentioning
confidence: 99%